THE CHALLENGES OF ONLINE LEARNING DURING PANDEMIC COVID 19 IN SMKN 5 SAMARINDA - Bali Geroda, Godefridus; Resna, Adinda Ayu (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
The success of teachers in conducting online learning in the Covid-19 pandemic condition is the ability of teachers to innovate in designing, concocting materials, media, learning methods, and suitable applications to the materials and methods. Moreover, teacher and students currently faced some challenges or difficulties in online learning. The challenges of online learning are difficulties faced by teacher and students which is all the factors involve in the challenges, such as the students or the teacher self and the technological that use in online learning. The purpose of this study is to find out the challenges of online learning during Pandemic Covid 19 in SMKN 5 Samarinda. This study used qualitative method. The result showed that almost all of the challenges that teachers faced in online learning (E- learning) are the unstable connection, the ability operation of the mechanism program, and the students' low interest or low motivation with online classes. However, the second major was communication barriers faced by teachers and students as the impact of unstable connection.